journal Factors related to the implementation of early initiation of breastfeeding for newborns in the working area of ​​the Sawah Besar Health Center, Bengkulu City: Factors related to the implementation of early initiation of breastfeeding for newborns in the working area of ​​the Sawah Besar Health Center, Bengkulu City - sera, Sera despa (JURNAL BESUREK JIDAN, 2025)
Early initiation of breastfeeding is giving newborn babies the opportunity to breastfeed themselves from their mother within the first hour of birth, the provision of early initiation of breastfeeding is still low at 36.84% in the Sawah Lebar Community Health Center, Bengkulu City. This research aims to determine the factors related to the implementation of IMD in the Sawah Lebar Community Health Center Work Area, Bengkulu City, the type of research used was descriptive research with a cross sectional approach. The number of samples taken was 54 mothers who had babies 0-6 months in the Sawah Lebar Health Center working area, Bengkulu City using the total sampling method, where the independent variables were measured (knowledge, support from health workers, husband/family support, type of delivery and place of delivery and The dependent variable is the implementation of Early Breastfeeding initiation in the work area of ​​the Sawah Lebar Community Health Center, Bengkulu City. The results of the bivariate analysis show that knowledge (p=0009) < 0.05, support from health workers (p=0.000) < 0.05, support from husband/family (p). =0.003) <0.05, type of delivery (p=0.000) <0.05 and place of delivery (p-0.000) <0.05 meaning there is a relationship between knowledge, support from health workers, support from husband/family, type of delivery, place of delivery regarding the implementation of early initiation of breastfeeding for newborns in the working area of ​​the Sawah Lebar Community Health Center, Bengkulu City. Suggestions for midwifery educational institutions, it is hoped that it will become material or counseling material for students during community service activities, as well as adding reading material and literature about early initiation of breastfeeding. Keywords: Knowledge, Support from health workers & husband, Type of delivery, Place of birth